Remotely sensed nighttime lights reveal China's urbanization process restricted by haze pollution - Liu, Shirao; Shi, Kaifang; Wu, Yizhen; Chang, Zhijian (Building and environment, 2021)
Under the background of China's active formulation and implementation of haze control policies, clarifying the relationship between the urbanization process (UP) and haze pollution (HP) is an important prerequisite for urban sustainable development. Previous studies have demonstrated the effect of the urbanization process on haze pollution (EUH) from different perspectives, but less attention has been given to the effect of haze pollution on the urbanization process (EHU). Thus, taking 247 prefecture-level cities in China as experimental subjects, this study has attempted to analyze whether HP has an effect on China's UP based on the National Polar-Orbiting Partnership's Visible Infrared Imaging Radiometer Suite (NPP-VIIRS) remotely sensed nighttime light data and econometric models. The results show that for every unit of HP increase, UP slows down by approximately 0.275 units, indicating that HP has restricted UP in China to a certain extent. In addition, in the eastern region of China, HP has also significantly restricted UP. However, in the central and western regions of China, EHU is not significant. Human capital (HC) has been proven to be an important transmission factor for EHU in large cities, medium-sized cities, and eastern developed areas. Based on the above analysis, the study proposed that haze control policies should be implemented according to the UP's characteristics in different regions, and the government should reasonably guide the flow of HC in different regions and promote coordinated development among regions. •Nighttime light data can be effectively for quantifying the urbanization process.•Haze pollution can restrict the urbanization process in China.•Human capital is an important transmission factors for the effect of haze pollution on the urbanization process.